PENGEMBANGAN BAHAN AJAR BERBASIS MIND MAPPING PADA PEMBELAJARAN IPA TEMA LINGKUNGAN SAHABAT KITA - Nurul Huda Panggabean; Amir Danis; Nadriyah (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Teaching materials can be designed according to the needs of students so that students are always interested in learning them. One method that is thought to be able to create an interesting, motivating and enjoyable learning atmosphere when students learn material is a mind map. This study aims to develop Mind Mapping-based teaching materials in science learning with our friends' environmental themes and to monitor the practicality and effectiveness of the teaching materials used. This study uses the Research and Development (R&D) method with a 4 D model, namely the model consists of four development stages, namely Define, Design, Develop, and Limited Disseminate. This research was conducted in June 2020 at the MIS Tarbiyatul Islamiyah Guppi Medan elementary school with a sample students in class V-B. Based on the results obtained, the total validity average was 4.68. Based on the criteria for average total validity, it can be said that the mind mapping-based teaching materials developed are very valid and the proportion of feasibility is 93.61%, with proportions for each aspect: content (91.82%), presentation (93.75%), mind mapping (98.00%) and graphics (90.87%). The analysis of students was obtained based on the results of the N -gain test where the average N-gain test results for class V - B were high with a result of 0.8 with student learning completeness 88.46%. Based on the student response questionnaire, the results can be obtained from the aspects that can be the aspect of interest with the respondent agreeing that the percentage is 49.36% and strongly agrees at 50.64%. The assessment of the material aspect obtained the results of the student's response to agree 75.96% and strongly agree 29.04%, the assessment of the language aspect obtained the results of agreeing 36.54% and 63.46% strongly agree. The conclusion of this research is that science with the theme of mind mapping-based friendly environment gets the validity of media experts and teaching materials experts and can be declared very feasible, practical and effective where students also experience completeness in learning, besides that the students' responses to teaching materials provide a response agree and totally agree. Abstrak Bahan ajar dapat didesain sesuai dengan kebutuhan siswa agar siswa senantiasa tertarik untuk mempelajarinya. Salah satu metode yang diduga mampu membuat suasana pembelajaran yang menarik, memotivasi siswa dan menyenangkan ketika siswa mempelajari materi adalah mind map. Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis Mind Mapping pada pembelajaran IPA Tema lingkungan sahabat kita dan mengetahui tingkat kepraktisan serta keefektifan bahan ajar yang digunakan. Penelitian ini menggunakan metode Research and Development (R&D) dengan model 4 D yaitu Model ini terdiri dari empat tahap pengembangan, yaitu Define, Design, Develop, dan Disseminate terbatas. Penelitian ini dilaksanakan pada bulan juni 2020 di sekolah dasar MIS Tarbiyatul Islamiyah Guppi Medan dengan sampel penelitian peserta didik kelas V B. Berdasarkan hasil yang diperoleh rata – rata total validitas adalah 4,68. Berdasarkan kriteria rata – rata total validitas dapat dikatakan bahwa bahan ajar berbasis mind mapping yang dikembangkan sangat valid dan persentase kelayakan 93,61%, dengan persentase untuk tiap aspek : isi (91,82%), penyajian (93,75%), mind mapping (98,00%) dan kegrafikan (90,87%). Analisis kognitif peserta didik diperoleh berdasarhan hasil uji N –gain dimana rata – rata hasil uji N – gain keseluruhan kelas V – B tergolong tinggi dengan hasil 0,8 dengan ketuntasan belajar siswa 88,46%. Berdasarkan anget respon siswa dapat diperoleh hasil dari aspek yang dinilai yaitu aspek ketertarikan dengan responden setuju persentasenya sebesar 49,36% dan sangat setuju sebesar 50,64%. Penilaian dari aspek materi diperoleh hasil respon siswa setuju 75,96% dan sangat setuju 29,04%, Penilaian dari aspek bahasa memperoleh hasil setuju 36,54% dan sangat setuju 63,46%. Kesimpulan dari penelitian ini yaitu bahan ajar IPA dengan Tema lingkungan sahabat kita berbasis mind mapping mendapatkan kevalidan dari ahli media dan ahli bahan ajar serta dapat dinyatakan sangat layak, praktis dan efektif dimana peserta didik juga mengalami ketuntasan dalam pembelajaran, selain itu respon peserta didik terhadap bahan ajar memberikan respon setuju dan sangat setuju. Kata Kunci : Pengembangan, Bahan Ajar, Mind Mapping, IPA, Sekolah Dasar